FACTORS AFFECTING ELECTRONIC MONEY (E-MONEY) SALES CASE STUDY IN BANKING ENTITIES IN INDONESIA - B Sundari; Cicilia Erly Istia; Renita Helena (Jurnal Ilmiah Ekonomi Bisnis, 2019)
Electronic money instruments with non-cash transactions continue to increase positively from year to year. This is also due to the launch of the national non-cash or cashless movement which has been widely applied, especially in Indonesia. This study aims to find out what factors influence e-money sales, especially in banking entities in Indonesia. This study uses multiple linear regression analysis method using SPSS 22, which aims to examine the relationship or effect of the dependent variable with the independent variable. The results of the study have found that in the partial sale of electronic money is only influenced by e-money marketing channels / partnerships. While ease of transaction, ease of top up, and type of design do not have an impact on e-money sales. Meanwhile, simultaneously, these factors have an impact on E-Money sales.